Analysis of the online microteaching practice of undergraduate physical education students - Raharjo, Hermawan Pamot; Kusuma, Donny Wira Yudha; Mohamed, Ani Mazlina Dewi; Rahayu, Tandiyo; Annas, Mohamad; Putra, Ranu Baskora Aji; Suripto, Agus Widodo; Kurniawan, Wahyu Ragil (LPMPP Universitas Negeri Yogyakarta, 2025)
Microteaching aims to ensure that students, as prospective educators, deserve to experience real teaching-learning situations. However, in light of recent advancements in educational technology and the increasing integration of online learning, it has been carried out online. This study aims to analyze students' competence in the online microteaching practice. This is classroom action research with three determined indicators as the basis for constructing a Likert scale questionnaire. 132/150 students are participating in this study. A descriptive statistical test was used to analyze the data, and students' opinions were also recorded to strengthen the results. Almost all students (98.4%) pretty much understand the microteaching practice, and quite well (97.7%) understand how to use the online application for online microteaching practice. Also, they are satisfied (99.9%) with the quality of online microteaching practices. In simple real-life learning practices, of the 132 respondents, only 68.1% mastered the characteristics of their students, 60.6% applied learning tools, and 60.6% implemented periodic assessments. We concluded that students' competence towards online microteaching practice is good, and they know the advantages and disadvantages of conducting an online class. However, the skills demonstrated by students in online situations were different and inconsistent with those exhibited in offline settings.